An introduction to DUIA: The database on urban inequality and amenities. - Frederico Roman Ramos (Public Library of Science (PLoS), 2021)
This article introduces DUIA, the Database on Urban Inequality and Amenities. DUIA includes data on the socio-economic development and amenities of 86 cities. The database especially covers cities outside the West, providing new opportunities for comparative research in fields suffering from a dearth of data. DUIA addresses three concerns that have not been resolved by other databases on cities. First, we draw upon remote sensing derived data from the Atlas of Urban Expansion to more accurately define city boundaries. Second, we draw upon survey data stored in IPUMS (Integrated Public Use Microdata Series) to include extensive, harmonized, and disaggregated data. Third, we use open source software and share our scripts to ensure transparency and replicability. DUIA includes information on dwelling and household characteristics, educational attainment, ownership of assets and appliances, and access to amenities. We provide illustrative analyses on asset inequality and water access to demonstrate the potential for the database. Although we also identify several limitations, DUIA represents a step forward in the systematic study of inequality and amenities over time and across cities.